1964
DOI: 10.3758/bf03342796
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intersession interval in shuttle- box conditioning of the guinea-pig

Abstract: ·AbstractSixty guinea-pigs were given 50 avoidance conditioning trials in a shuttle-box and then retested either 0, I, 24, 48, of 168 hr. later. Little improvement in performance was observed within sessions but animals retested at 48-and 168-hr. intersession intervals were substantially better than all others. ProblemIn a study of shuttle-box avoidance conditioning in guinea-pigs, the authors found that animals made few avoidance responses in 50 or even 150 trials and showed little or no improvement in perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

1967
1967
1972
1972

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…These earlier works and the present study c1early demonstrate a facilitatory effect of large bilateral hippocarnpallesions on the performance of a two-way shuttle-box problem. The appearance of this phenomenon in the present study is particularly impressive, considering the normally poor performance displayed by guinea pigs on tasks of this nature (Evoni~ ~ Brimner, 1967;Webster & Rabedau, 1964;Webster et al, 1965). It may be that this is a general phenomenon in rodents, even those ordinarily unable to learn such tasks.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…These earlier works and the present study c1early demonstrate a facilitatory effect of large bilateral hippocarnpallesions on the performance of a two-way shuttle-box problem. The appearance of this phenomenon in the present study is particularly impressive, considering the normally poor performance displayed by guinea pigs on tasks of this nature (Evoni~ ~ Brimner, 1967;Webster & Rabedau, 1964;Webster et al, 1965). It may be that this is a general phenomenon in rodents, even those ordinarily unable to learn such tasks.…”
supporting
confidence: 54%
“…Training sessions were spaeed 24 h apart. This particular training procedure was expected to produce very little learning of the avoidance response in normal Ss (Evonic & Brimer, 1967;Webster & Rabedau, 1964;Webster, Brimer, & Evonic, 1965). An Esterline Angus event recorder was used to record avoidance responses, spontaneous crossing, and response latency.…”
mentioning
confidence: 99%
“…In addition to differences in initial performance, the present study also demonstrated the sharp increase in avoidance level following a 48-h rest as originally reported by Webster & Rabedeau (1964). Of interest here is the fact that the intersession improvement was greater for the first-session low and medium groups than for the first-session high group and that it was independent of second-session shock intensity_ Thus, the factor that interferes with performance does not disappear after 48 h if the initial training is conducted with very high shock.…”
supporting
confidence: 69%
“…Another way by which effective reinforcement may be increased is to provide a 48-hr, interval between shuttle-box sessions since fear of apparatus cues, but not fear of the discrete CS, shows forgetting in this length of time following conditioning (Goldman, 1969;McAllister & McAllister, 1968). Data reported by Webster and Rabedeau (1964) and by Rabedeau and Webster (1970), which show an improvement in shuttle-box avoidance learning in guinea pigs after a 48-hr, intersession interval, are consistent with this interpretation. In the latter study it was reported that the improvement in performance was greater in low-and medium-than in high-shock groups.…”
Section: Discussionmentioning
confidence: 79%